„A trip organised for children is not a serious matter“? Summer treatment camps for the Belgian-German borderlands (1919–1939). - Venken, Machteld (Childhood, 2025)
„Although the children whose rural homelands transitioned from German to Belgian state sovereignty following the First World War were not the typical demographic targeted for preventive air treatments against tuberculosis, they were overrepresented in treatment camps in both Belgium and Germany. Nation-state representatives provided public and private (although partly state subsidized) treatment camps to restore the physical vitality, ethical integrity, and national allegiances of the minors. The parallel competitive offer took the form of a cross-border mixed economy of child welfare. Borderland residents either opportunistically supported the Belgian or German initiatives, or provided their own alternatives to protect their children from indoctrination.“
Keywords: Heilanstalt; Jugend; Kind; Nationalbewusstsein; Nationalismus; Nationenbildung; Verschickung

Von Staatsgrenzen zu nationalen Grenzen - Nordman, Daniel (Die Grenze als Raum, Erfahrung und Konstruktion. Deutschland, Frankreich und Polen vom 17. bis zum 20. Jahrhundert, 2007)
Keywords: Nationalbewusstsein; Nationalismus; Nationenbildung; Staatsgrenze